Design of self-dispersible charged-polymer building blocks for waterborne polyurethane dispersions. (April 2018) - Jiménez-Pardo, I.; Sun, P.; van Benthem, R.A.T.M.; Esteves, A.C.C.
Graphical abstract: Highlights: A more efficient and economic route to obtain waterborne PUDs is described. Well-defined DMPA-PCL self-dispersible polymers are synthesized by CROP. The diisocyanate amount is reduced up to 63% in comparison to conventional methods. Waterborne PU colloidal stability is not compromised by the new method. Abstract: Waterborne polyurethane dispersions (PUDs) currently have a wide spectrum of applications as coating resins for biomedical products, food packaging, cosmetics and traditional coatings. At present, PUDs are commonly prepared by the "prepolymer extension" method in which isocyanate terminated self-dispersing prepolymers are dispersed in water, followed by chain extension via the terminal isocyanate groups. The preparation of such self-dispersing prepolymers from diisocyanates, ionizable diols and non-ionizable diol blocks is a stochastic process with poor control over the prepolymer molecular weight and functionality distribution, which may result in sub-optimal properties of the PUDs. We investigated a new route in which we prepare ionizable macro-diol blocks, out of hydrophobic polycaprolactone (PCL) blocks, covalently bonded to the ionizable diol dimethylolpropionic acid (DMPA) via Cationic Ring Opening Polymerization (CROP), which subsequently are coupled via isocyanate chemistry to prepare the PUDs. During the preparation of the pre-polymer the reaction was steered towards a DMPA- diblock -PCL macro-emulsifier, with controlled molecular weight and molecular weight distribution. The waterborne PUDs prepared afterwards with the designed DMPA-PCL building block showed the desired particle size, Zeta-potential and improved stability over time, when compared to a highly analogous traditional system. Furthermore, the preparation of the DMPA-PCL self-dispersing block allowed reducing up to 63% the amount of diisocyanate used compared to the commonly used "pre-polymer extension" method, without sacrificing long-term colloidal stability. The interesting features of the new DMPA-PCL self-dispersible building blocks ensure a wide range of applications, via a safer, more efficient and economic preparation route.